A população transgênero no ambiente universitário: desafios - Silva, Giannini Ferreira de Freitas (Universidade Federal Rural do Semi-Árido, 2018)
Education is a fundamental human right fixed in our Federal Constitution, which must be a universal guarantee, that means, for all people, regardless of class, race, gender identity or sexuality. However, despite this commandment, transgender people face huge difficulty in staying and access to higher education, and their presence in these institutions is still greatly reduced. Based on this, the present work seeks to understand the difficulties they face in accessing higher education, as well as what obstacles they encounter when they are in universities. For this reason, the methodological resource used for data collection was a questionnaire directed to the transgender people of UFERSA and to those that are not in higher education. As the number of transgender students within the researched institution is small and, based on the assumption that prejudice and discrimination is one of the main obstacles to their permanence, it was also decided to apply questionnaires with the cisgender students to understand their perceptions about the presence of transgender people in universities. The research had relevant conclusions that indicate challenges for entering higher education, since the transgender people are strongly marginalized in our society, ranging from prejudice and discrimination, unemployment and low life expectancy due to transphobia. On the other hand, there was a strong prejudice and lack of knowledge coming from cisgender students about transgender people. The research also assesses the challenges that transgender people face in everyday life at UFERSA, such as discrimination, looks, transphobic jokes, among others
Artigo Acadêmico
Keywords: Educação; Ensino Superior; Transgêneros; Inclusão e Permanência; Education; Higher education; Transgender; Inclusion and Permanence; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA